Lactic acidosis and abnormal liver function in advanced HIV disease. Issue 2 (1st April 2002) - Shahmanesh, M; Cartledge, J; Miller, R
Abstract : A 48 year old man receiving HAART presented with late stage HIV disease, non-specific symptoms, a normal sized liver, ascites, and lactic acidosis. Following a failed liver biopsy worsening acidosis developed, requiring ICU support. Progressive liver failure occurred. Endoscopy showed oesophageal varices and a transjugular liver biopsy showed non-cirrhotic cholestasis; findings that were ascribed to HAART.